Discursive markers' communicative-pragmatic characteristics (Journal of Pedagogical Inventions and Practices, 2024)
Nowadays, the term ‘discourse’ is one of the most actively used terms in global linguistics and several other social and humanitarian fields. There are also several related concepts, one of which is discursive markers. In this article, the place of discursive markers in the speech communication system, their communicative-pragmatic aspects, and examples taken from literary discourse are analyzed. The role and significance of discursive markers in expressing the speaker’s intensity are highlighted.